The critical soil P levels for crop yield, soil fertility and environmental safety in different soil types - Bai, Zhaohai; Li, Haigang; Yang, Xueyun; Zhou, Baoku; Shi, Xiaojun; Wang, Boren; Li, Dongchu; Shen, Jianbo; Chen, Qing; Qin, Wei; Oenema, Oene; Zhang, Fusuo (Plant and soil, 2013)
Background and aims Sufficient soil phosphorus (P) is important for achieving optimal crop production, but excessive soil P levels may create a risk of P losses and associated eutrophication of surface waters. The aim of this study was to determine critical soil P levels for achieving optimal crop yields and minimal P losses in common soil types and dominant cropping systems in China. Methods Four long-term experiment sites were selected in China. The critical level of soil Olsen-P for crop yield was determined using the linear-plateau model. The relationships between the soil total P, Olsen-P and CaCl₂-P were evaluated using two-segment linear model to determine the soil P fertility rate and leaching change-point. Results The critical levels of soil Olsen-P for optimal crop yield ranged from 10.9 mg kg⁻¹ to 21.4 mg kg⁻¹, above which crop yield response less to the increasing of soil Olsen-P. The P leaching change-points of Olsen-P ranged from 39.9 mg kg⁻¹ to 90.2 mg kg⁻¹, above which soil CaCl₂-P greatly increasing with increasing soil Olsen-P. Similar change-point was found between soil total P and Olsen-P. Overall, the change-point ranged from 4.6 mg kg⁻¹ to 71.8 mg kg⁻¹ among all the four sites. These change-points were highly affected by crop specie, soil type, pH and soil organic matter content. Conclusions The three response curves could be used to access the soil Olsen-P status for crop yield, soil P fertility rate and soil P leaching risk for a sustainable soil P management in field.